Influence of Steel Fiber Addition on Workability & Mechanical Behavior of High Performance Concrete - Abubakar, Abdulhameed Umar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
In this study, the mechanism of crack propagation in concrete at discontinuity stress region under uniaxial compression was investigated and an attempt was made to determine the microcracking behavior of high-performance concrete with steel fiber addition at 7 different fiber volume (Vf) under two aspect ratios. For this purpose, fourteen different concrete mixes with steel fiber addition for 60 and 75 aspect ratio, each changing in proportions from 0.5 - 2.0 % with 0.25 % intervals were designed based on high performance concrete principles. Microcracking behavior of the produced concretes were analyzed by selecting two stress points before the linearity, the linearity end point, and one point after the end of the linearity using the tangent points (deviation from linearity) of load – time diagram. Findings revealed that in terms of workability, with increasing Vf addition and aspect ratio, VeBe time increases exponentially; slump and compacting factor decreases linearly, and an inverse relationship exist between yield stress and slump. It is hereby suggested that in terms of workability for this kind of mixes, a combination of parameters should be considered instead of a single parameter to characterize workability. Compressive strength increases with increase in fiber addition in aspect ratio 60, while in aspect ratio 75, the increment was up to 1.0 % fiber addition level, but it was still higher than the reference specimens without fiber addition. Tensile strengths in the form of splitting and flexural tensile strength increased with fiber addition in both cases; however, the flexural strength presented results with higher strength. Area under the load – deflection diagrams increases with increase in fiber volume and aspect ratio, an indication of the improvement in toughness of the composite. Fracture energy increases with increase in fiber volume and compressive strength, an indication of high energy required in extending cracks. Characteristic length also increases showing the increased ductility of the composite. Residual tensile strength measured indicated that there was strain hardening behavior due to the fiber addition resulting in tensile strength gain instead of tensile strength loss in concrete with fiber addition. Results from the load – time diagram used to determine the end of the linear portion of the graph indicates that the end of ascending portion (linearity) lies within 85 – 91% of the ultimate strength, aggregate cracking was the dominant failure mode up to the end of linearity as oppose to bond cracks due to improvement in the matrix quality. Failure pattern similar to what is obtained in compressive loading is applicable here at linearity end point and post linearity with extensive damage perpendicular to the casting direction. The presence of the steel fiber improved the extensive failure pattern of cracks observed at aspect ratio 60 and 75 where it changes from macrocracks to a branched network of microcracks especially at higher fiber dosage. Critical width of the cracks measured at linearity end point was within the range of 0.01 mm – 0.07 mm. The findings of this study will go a long way in helping our understanding of the microcracking in concretes with fiber addition which is the next frontier in structural concrete.

ÖZ: Bu çalışmada; çelik elyaflı yüksek performanslı beton (HPC), tek eksenli basınç yükü altındada çatlak yayılımı mekanizması, betona iki farklı boy oranı ve yedi farklı lif hacim (Vf) ilavesi durumları için incelenmiştir. Bu amaçla, yüksek performanslı beton prensiplerine dayanarak, her biri % 0,5 - % 2,0 arasında, % 0,25 aralıklarla değişen hacim oranlarında, 60 ve 75 en-boy oranı için çelik lifli, on dört farklı beton karışımı tasarlandı. Üretilen betonların mikro çatlak davranışları; betonun basınç yük-deformasyon eğrisi eğim takibinden tesbit edilmiş olan, 4 farklı gerilme noktasında (doğrusallık bitiş noktası, 2 nokta doğrusallık bitiş noktasından önce ve de 1 nokta sonra) analiz edilmiştir. Bulgular, artan lif hacim ilavesi ve en-boy oranı ile VeBe zamanının katlanarak arttığını, çökme ve sıkıştırma faktörü değerlerinin ise doğrusal olarak azaldığını göstermiştir. Akma gerilmesi ve çökme değerleri arasında ters bir ilişki olduğu da gözlemlenmiştir. Bu tür karışımlarda, işlenebilirliği karakterize etmek için tek bir parametre yerine parametrelerin bir kombinasyonu düşünülmelidir. En-boy oranı 60'da; lif ilavesindeki artışla birlikte basınç mukavemeti artarken, en- boy oranı 75’te artış, % 1 lif ekleme seviyesine kadar devam etmiştir. Fakat yine de lif ilavesi olmayan referans numunelerden daha yüksek çıkmıştır. Her iki durumda da lif ilavesiyle yarma, eğilme ve çekme mukavemeti gibi gerilme mukavemetleri artmıştır; Bununla birlikte, sunulan eğilme mukavemeti daha yüksek mukavemet ile sonuçlanmaktadır. Yük altındaki alan diyagramları, lif hacim ve en-boy oranındaki artışla artar. Bu, kompozitin sağlamlığındaki iyileşmenin bir göstergesidir. Kırılma enerjisi, lif hacmindeki artış ve basınç dayanımı ile artar. Bu, çatlak gelişimi için gerekli olan yüksek enerjinin bir göstergesidir. Karakteristik boy uzaması, kompozitin artan sünekliliğini de gösterir. Lif ilavesiyle betonda gerilme mukavemeti kaybı yerine gerilme mukavemeti kazancı oluşmuştur. Yük - zaman diyagramından, grafiğin doğrusal kısmının (% 85 - % 91) basınç mukavemetine tekabül ettiği gözlemlenmiştir. Çelik lifin mevcudiyeti ile; özellikle yüksek lif dozajında, makro çatlak yerine, daha fazla sayıda dallanmış mikro çatlak oluşmuştur. Bu her iki en-boy oranında (60 ve 75) da ve de artan miktarlarda gözlemlenmiştir. Yük - zaman diyagramında, grafiğin doğrusal kısmına denk gelen basınç gerilmesi altında ölçülen çatlakların kritik genişliği, 0.01 mm - 0.07 mm aralığında ölçülmüştür. Bu çalışmanın bulguları, lif içeren yapısal betonda mikro çatlakların oluşması, yayılması, kritik ebat ve konuma ulaşmaları konusunun daha iyi anlaşılmasına iyi bir yol gösterici olacaktır.
Doctor of Philosophy in Civil Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2018. Co-Supervisor: Assoc. Prof. Dr. Khaled Marar and Supervisor: Assist. Prof. Dr. Tülin Akçaoğlu.
Keywords: Civil Engineering; Steel Fiber Concrete; Capital structure; Dynamic trade-off theory; Oil and gas companies; Oil production cost; Oil price; Resource curse